Studies on flow from convergent nozzle with sudden expansion and control effectiveness under the influence of micro jets - Ashfaq, Syed; Khan, Sher Afghan (International Journal of Research in Mechanical Engineering and Technology, 2013)

(untitled)
Sudden expansion fluid flow is of great importance. In the present study experiments are conducted to control the base pressure from a convergent nozzle. Active control in the form of micro jets are used as an active control of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region. Area ratio of the present study i.e. ratio of area of suddenly expanded duct to nozzle exit area studied is 4.84. Nozzle pressure ratio (NPR) and length-to-diameter (L/D) ratio are main geometric and inertia parameters considered in the present study. Accordingly, Tests are conducted for NPR in the range of 1.5 to 3.0, in the steps of 0.5. L/D ratio of the enlarged duct was considered are from 10 to 1, and tests were carried out for L/D 10, 8, 6, 5, 4, 3, 2 and 1. From the experimental studies, it is found that, unlike in the case of passive controls, the favourable pressure gradient does not ensure augmentation of the control effectiveness for active control in the form of micro jets. It is found that it is case sensitive as with increase in the NPR the wave pattern at the base region will be changing continuously. Further, it is found that the micro jets are activated they do not disturb the flow field in the enlarged duct.